Biochemistry - Voet, Donald (J. Wiley & Sons, 1995)
This comprehensive text thoroughly explains basic biochemical concepts while offering a unified presentation of life and its variation through evolution. Incorporates both classical and current research to illustrate the historical source of much of our biochemical knowledge. Contains a wealth of biochemical applications such as agricultural, pharmaceutical, medical and forensic. This edition has been updated to reflect the enormous advances in molecular and protein structure. Features increased emphasis on human disease, more end-of-chapter problems and extensive use of molecular biological techniques.